2016
DOI: 10.1155/2016/2410573
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Naturally Etched Fission Tracks and Alpha-Recoil Tracks in Submarine Glasses: Reevaluation of a Putative Biosignature for Earth and Mars

Abstract: Over the last two decades, conspicuously “biogenic-looking” corrosion microtextures have been found to occur globally within volcanic glass of thein situoceanic crust, ophiolites, and greenstone belts dating back to ~3.5 Ga. These so-called “tubular” and “granular” microtextures are widely interpreted to representbona fidemicrobial trace fossils; however, possible nonbiological origins for these complex alteration microtextures have yet to be explored. Here, we reevaluate the origin of these enigmatic microtex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 215 publications
0
10
0
Order By: Relevance
“…These initial materials and conditions, though uncommon on Earth today, are geochemically plausible during Archaean times (García-Ruiz 1998). French & Blake (2016) similarly found a plausible abiotic formation mechanism for microfossils by examining submarine glasses from the western North Atlantic Ocean. By combining petrographic and electron microscopic observations with theoretical models of radiation damage from uranium and thorium decay, French & Blake (2016) found that tubular and granular microfossils can be formed by preferential seawater corrosion of damage trails left by fission fragments.…”
Section: Microfossilsmentioning
confidence: 85%
“…These initial materials and conditions, though uncommon on Earth today, are geochemically plausible during Archaean times (García-Ruiz 1998). French & Blake (2016) similarly found a plausible abiotic formation mechanism for microfossils by examining submarine glasses from the western North Atlantic Ocean. By combining petrographic and electron microscopic observations with theoretical models of radiation damage from uranium and thorium decay, French & Blake (2016) found that tubular and granular microfossils can be formed by preferential seawater corrosion of damage trails left by fission fragments.…”
Section: Microfossilsmentioning
confidence: 85%
“…However, how biosignatures of subsurface communities might be preserved over time remains unknown. Although it has been suggested that microtubules observed in some subsurface basalts might be a biosignature (Fisk et al, 1998 ; Staudigel et al, 2008 ), the biological origin of these structures remains unproven, and alternative explanations have been proposed (French and Blake, 2016 ). Potential biosignatures that could persist for millions to billions of years in the subsurface have not yet been identified.…”
Section: Mars Analog Environments On Earthmentioning
confidence: 99%
“…The Yamato microtextures were previously compared by White et al () to candidate biosignatures found in altered volcanic glasses; however, there is now a maturing body of work that has questioned the role of microbes in the formation of terrestrial “bioalteration” textures. Many early workers favoured a microbial origin for so‐called bioalteration textures found in seafloor glasses (e.g., Banerjee & Muehlenbachs, ; Fisk, Giovannoni, & Thorseth, ; Staudigel et al, ; Thorseth, Furnes, & Heldal, ), but an increasing number of petrological and experimental studies have questioned the contribution of microbes to seafloor volcanic glass dissolution and suggested a range of possible abiotic mechanisms (e.g., Alt & Mata, ; Fisk, Crovisier, & Honnorez, ; Fisk, Popa, & Wacey, ; French & Blake, ; Knowles, Wirth, & Templeton, ), particularly for the granular microalteration textures (McCollom & Donaldson, ), and also for microtextures found in ancient meta‐volcanic glasses (Grosch & McLoughlin, ; Lepot, Benzerara, & Philippot, ). This study expands the range of known abiotic alteration processes recorded by olivine microalteration textures, and reports high‐magnification imaging and chemical mapping data not yet reported from similar olivine microalteration textures found in terrestrial ultramafic rocks (Fisk et al, ).…”
Section: Discussionmentioning
confidence: 99%